Clinical Characteristics and Surgical Treatment of Intraorbital Foreign Bodies in a Tertiary Eye Center. Issue 6 (September 2015) - Chen, Jingchang; Shen, Tao; Wu, Yongjuan; Yan, Jianhua
<x xml:space="preserve">Abstract</x> Purpose: Intraorbital foreign body is relatively rare and therefore is often misdiagnosed in clinical practice. The purpose of this report is to summarize the clinical features of intraorbital foreign bodies and their surgical management. Methods: A retrospective study of clinical cases. Clinical manifestations, imaging findings, and surgical treatments in patients with intraorbital foreign bodies, who were seen at the Zhongshan Ophthalmic Center of Sun Yat-sen University between January 2002 and July 2013, were retrospectively reviewed. Results: Of the 22 cases reviewed, 19 were men and 3 women with a mean age of 22.2 years. Patients ⩽14 years of age accounted for 45.5% of the cases. The right orbit was affected in 10 patients and the left in 12 patients. Organic intraorbital foreign bodies comprised 72.7% of the patients. Foreign body locations within the orbit were superior (40.9%), medial (27.3%), lateral (18.2%), and inferior (9.1%). Half of the patients presented with preoperative visual impairments and 45.5% with limited motility/strabismus and ptosis. Orbital imaging revealed that organic foreign bodies consisted of a strip, rod-like high-density image surrounding soft tissue on CT scan and hypointense on both T1WI and T2WI with MRI images. Complete removal of the intraorbital foreign body was accomplished by anterior orbitotomy in 21 patients and lateral orbitotomy in the remaining patients. Removal was achieved in a single surgery for 21 patients whereas 2 surgeries were required for the remaining patients. No postoperative complications were reported in any of the patients. Conclusions: Intraorbital foreign bodies requiring surgical removal mostly involved organic foreign bodies. These were most commonly found in male children. Orbital imaging played a critical role for an accurate presurgical diagnosis. Anterior orbitotomy provided the best surgical outcomes.